Circular RNA NF1-419 enhances autophagy to ameliorate senile dementia by binding Dynamin-1 and Adaptor protein 2 B1 in AD-like mice - Diling, Chen (Aging (Albany NY), 2019)
Recent studies have demonstrated circular RNAs (circRNAs) to be widely expressed and to have important physiological functions. However, the expression, regulation, and function of circRNAs in neuroglial cells are unknown. Herein, we characterized the expression, regulation, and function of circRNAs in astrocytes. Astrocyte circRNAs were identified by computational analysis of newborn SD rat primary astrocytes cultured with 20 g/L D-galactose. In this manner, 7376 circRNAs were identified, among which most circRNAs (5754) were derived from annot_exons, whereas 27 were antisense, 853 were exon/intron, 329 were intergenic, 41 were intronic, and 372 were one exon. Among these, circNF1-419 was demonstrated to regulate autophagy, in over-expressing circNF1-419 transfected astrocytes, through the PI3K-I/Akt-AMPK-mTOR and PI3K-I/Akt-mTOR signaling pathways. An adenovirus associated virus packaging system (virus titer 1 ×10(12)), over-expressing circNF1-419 and injected into mouse cerebral cortex, showed autophagy enhancing activity by binding the proteins Dynamin-1 and Adaptor protein 2 B1 (AP2B1). This binding regulated aging markers (p21, p35/25, and p16) and inflammatory factors (TNF-α and NF-κB), and reduced the expression of Alzheimer’s disease marker proteins (Tau, p-Tau, Aβ(1-42), and APOE), which delayed senile dementia. Transcriptome analysis of the brain showed that circNF1-419 improved other signaling pathways, especially those related to the synapses of SAMP8 mice. These findings provide novel insights into circNF1-419 and its potential usefulness for the diagnosis and treatment of dementia by regulating Dynamin-1 and AP2B1 mediated autophagy.